To the stars : the story of NASA - Miller, Ron, 1947- (Twenty-First Century Books, 2026)
"In 1915 the US Congress created the National Advisory Committee for Aeronautics (NACA). The committee's first goal was to support the development of aviation. But in the wake of the space race with the Soviet Union that began in the late 1950s, NACA became NASA--the National Aeronautics and Space Administration. From novel technology to international collaboration to scientific research, NASA has become a global leader in space exploration. It even enabled people to walk on the moon for the first time. But how did NASA get here? What has the agency accomplished along the way? Ron Miller explains NASA's rich history through a curious, detailed exploration of its successes and failures. Discover the full story of how NASA came to be and learn about its many accomplishments and the scientists and technology behind them. Then look to the future through NASA's Artemis program and their next big goal of sending astronauts to Mars" --